Osteopontin--a possible anchor of osteoclasts to bone. - Reinholt, F P (1990)
A key event in bone resorption is the binding of osteoclasts to the mineral matrix of bone surfaces. A candidate for mediating this binding is osteopontin, a major cell- and hydroxyapatite-binding protein synthesized by osteoblasts. In support of this hypothesis is the fact that the synthesis of osteopontin is stimulated by calcitriol (1,25-dihydroxy-vitamin(D3), a substance that induces bone resorption. The present study demonstrates that osteopontin is highly enriched at regions of the bone surface where osteoclasts are anchored. Furthermore, the vitronectin receptor, which has known specificity for osteopontin, is shown preferentially localized at the corresponding area of the osteoclast plasma membrane. The results thus support the hypothesis that osteoclasts when resorbing bone are anchored by osteopontin bound both to the mineral of bone matrix and to a vitronectin receptor on the osteoclast plasma membrane.